Supporting Carers of Children and Adolescents with Eating Disorders in Austria (SUCCEAT): Study protocol for a randomised controlled trial. (6th May 2018) - Franta, Claudia; Philipp, Julia; Waldherr, Karin; Truttmann, Stefanie; Merl, Elisabeth; Schöfbeck, Gabriele; Koubek, Doris; Laczkovics, Clarissa; Imgart, Hartmut; Zanko, Annika; Zeiler, Michael; Treasure, Janet; et al.
Abstract: Supporting Carers of Children and Adolescents with Eating Disorders in Austria (SUCCEAT) is an intervention for carers of children and adolescents with anorexia nervosa and atypical anorexia nervosa. This paper describes the study protocol for a randomised controlled trial including the process and economic evaluation. Carers are randomly allocated to one of the 2 SUCCEAT intervention formats, either 8 weekly 2‐hr workshop sessions ( n = 48) or web‐based modules ( n = 48), and compared with a nonrandomised control group ( n = 48). SUCCEAT includes the cognitive‐interpersonal model, cognitive behavioural elements, and motivational interviewing. The goal is to provide support for carers to improve their own well‐being and to support their children. Outcome measures include carers' distress, anxiety, depression, expressed emotions, needs, motivation to change, experiences of caregiving, and skills. Further outcome measures are the patients' eating disorder symptoms, emotional problems, behavioural problems, quality of life, motivation to change, and perceived expressed emotions. These are measured before and after the intervention, and 1‐year follow‐up.